Ion transport control in electrolytes via electrochemical doping - Zhiwei Li; Yinghong Xu; Wanheng Lu; Xinglong Pan; Langyuan Wu; Wei Li Ong; Netanel Shpigel; Gang Chen; Ghim Wei Ho (Proceedings of the National Academy of Sciences, 2026)
Doping to control carrier (electron or hole) transport is foundational to modulate the properties of semiconductors, enabling the development of homojunctions and heterojunctions for integrated electronics. Unlike semiconductors with unipolar charge-carrier dominance, both cations and anions in electrolytes are mobile, which is undesirable for many applications. Here, we report a universal strategy to dope electrolytes such that the ion transport can be unipolar by incorporating electroactive polymers within hydrogels that interact discriminately with one type of ion via redox and binding mechanisms, leaving the counterions mobile. This transforms the system into an active, selective conductor that directs ion flow with high precision. We demonstrate the generality of this strategy using a wide range of electroactive polymers and ions. Particularly, we use emeraldine base and leucoemeraldine base, derived from polyaniline to create both n-type and p-type conductors with high ion selectivity. This electrolyte doping strategy has significant implications beyond the developed thermoelectrochemical devices with boosted performance, with potential applications in supercapacitors, batteries, and electrochemical sensors.